PERAN MANAJEMEN PEMBELAJARAN DALAM MENINGKATKAN PRESTASI AKADEMIK - Ami Putri Nadia; Mizan Mizan; Zubaidah Zubaidah (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
Learning management plays an important role in improving students' academic achievement by creating a conducive and organized learning environment. This article discusses the relationship between learning management and academic achievement, which is influenced by internal factors, such as student motivation and cognitive ability, as well as external factors, such as family support and learning quality. The method used is a literature study by reading various sources that discuss education management and academic achievement. The results of the study show that student academic achievement does not only reflect the results of numerical evaluation, but also the mastery of competencies such as critical thinking, creativity, and cooperation. The use of relevant learning strategies, such as project-based learning and technology, can increase student engagement in the learning process. In addition, teachers' competence in managing the classroom and providing constructive feedback are also key to successful learning. This article recommends the implementation of a holistic approach that involves support from various parties, including families, teachers and the school environment, to create optimal learning conditions and support maximum student academic achievement.